De l'office à la dignité: l'écolâtre cathédral en France septentrionale du IXe au XIIIe siècle - Kouamé, Thierry (Education and society in the Middle Ages and Renaissance, 2021)
"This book traces the history of one of the central actors in the transformation of the Western educational system between the 9th and 13th centuries: the cathedral schoolmaster. Originally responsible for running the episcopal school, this ecclesiastical official eventually became a true school administrator with a territorial monopoly and coercive powers, including in particular issuing 'licentia docendi' to masters under his jurisdiction. Using a wide range of sources and taking in thirty-nine dioceses in northern France, the study analyses the construction of the office from the Carolingian period, the place of the schoolmaster within the canonical community and in feudal society, and the institutionalisation of his function with the Gregorian Reform and the birth of universities"--